Transfer Teknologi Pasteurisasi sebagai Strategi Peningkatan Daya Saing Produk Susu Kambing Etawa di Lumajang - Agus Purnomo; Habiddin; Muhammad Aris Ichwanto (Jurnal Pemberdayaan Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) engaged in Etawa goat farming have significant potential to support food security and strengthen local economic development in Lumajang Regency. However, the partner MSME, Goatzilla Farm located in Senduro District, continues to face challenges in processing fresh goat milk, particularly related to limited shelf life and inadequate hygiene standards. This community engagement program aims to enhance MSME competitiveness through the transfer of pasteurization technology that is efficient, easy to operate, and suitable for local production capacity. The program was implemented through technical training, demonstration of pasteurization equipment, and on-site mentoring on hygienic milk processing practices at the partner’s production facility. The results indicate improved technical understanding and operational skills among the MSME actors, accompanied by enhanced product quality, as reflected in an increase in milk shelf life from 1–2 days to 5–7 days under refrigerated storage. Furthermore, the improved product quality strengthened consumer trust and created opportunities for product diversification. Overall, this initiative contributes to strengthening MSME competitiveness through technological innovation and supports sustainable local economic development in Lumajang Regency.